1981
DOI: 10.1289/ehp.813993
|View full text |Cite
|
Sign up to set email alerts
|

Chemically induced leukemia in humans.

Abstract: The human population may be exposed to potentially leukemogenic agents, either in the form of drugs and food additives or as environmental contaminants and pollutants. However, in spite of the large number and diversity of these chemicals, only a few have been implicated as human leukemogens. One such agent is benzene, a known bone marrow depressant. A number of case reports have associated chronic exposure to this agent with the development of acute leukemia, as have several epidemiologic surveys. Treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 103 publications
2
2
0
Order By: Relevance
“…In the current study, we found that immunosuppression was frequently mentioned in the literature concerning rat carcinogens affecting the hematopoietic system. This is an interesting finding, which is also in line with the known mechanisms of human carcinogens affecting this organ ( Adamson and Seiber, 1981 ; IARC, 2015 ). An association between immunosuppressant drugs and development of cancer in the hematopoietic system (lymphomas) in humans has also been shown previously ( Bugelski et al, 2010 ).…”
Section: Discussionsupporting
confidence: 75%
“…In the current study, we found that immunosuppression was frequently mentioned in the literature concerning rat carcinogens affecting the hematopoietic system. This is an interesting finding, which is also in line with the known mechanisms of human carcinogens affecting this organ ( Adamson and Seiber, 1981 ; IARC, 2015 ). An association between immunosuppressant drugs and development of cancer in the hematopoietic system (lymphomas) in humans has also been shown previously ( Bugelski et al, 2010 ).…”
Section: Discussionsupporting
confidence: 75%
“…. .iu-'S.. Cronkite et al (29) Doubling time: Seems to be about 2 days from a survival of 1 0% and 4 days from a survival of 20%; times close to the previous study of Cronkite et al (27).…”
Section: Methodssupporting
confidence: 72%
“…In 1961, Cronkite (26) concluded that any agent which produces marrow aplasia is a "putative leukemogen." Later, Adamson and Seiber (27) j.…”
Section: Methodsmentioning
confidence: 96%
“…An increased risk of leukemia has been reported among patients treated with immunosuppression or cancer chemotherapy. 6 The study of the etiologic role of environmental exposures in the development of leukemias has some advantages over those of most solid tumors. The lifespan of leukocytes of myeloblast origin is short; consequently, although they are considered less active in proliferation>* mutated stem cells may form clones of transformed cells that are liberated from bone marrow shortly after cell transformation.…”
mentioning
confidence: 99%